Programa basado en la modificabilidad estructural cognitiva y su influencia en el desarrollo cognitivo de estudiantes incluidos de educación primaria - Trujillo - 2015 - Ushiñahua Guabloche, Yrma (2017)
ABSTRACT This is a concurrent mixed research whose purpose was to determine how the Modifiability Based on Structural Cognitive program influences cognitive development of primary school students Trujillo - 2015. The sample was selected using a discretionary non-probability sample by convenience. The program is based on the theory of Structural Cognitive modifiability by the israeli psychopedagogue Reuven Feuerstein, who says that the human body has its own ability to modify the structure of its operation, also it supports the modifiability of cognitive structures, resulting from combining cognitive components, motivational and affective, considering these last ones as the essential factors for good cognitive functioning. The design was concurrent triangulation techniques and the following instruments: observation, by registration of guidelines of cognitive and attitudinal development (mental map); the survey with application of pre and post test (Wise IV), the interview with semi-structured interview guides and focus group guide, applied at the beginning and at the end of the program. Quantitative data were organized in tables calculated statistical averages and standard deviation of the scores obtained by students in the pre and post test and registration guidelines of cognitive and attitudinal development. The qualitative data from the responses obtained in the interview guides and group focus applied to mothers and teachers of the participants were organized into categories and subcategories to analyze and lay the foundations of them according to the approaches of the theory of cognitive structural modifiability, which formed the theoretical basis of this study. The hypothesis was verified by the non-parametric Wilcoxon signed rank. The results obtained after triangulating the data showed that the program influenced very significantly in the cognitive development of the participants.